Efektivitas Acceptance and Commitment Therapy pada Remaja: A Systematic Review - Anak Agung Sri Sanjiwani; Ni Luh Khrisna Ratna Sari (Universitas Kristen Maranatha, 2025)
The dynamics of the developmental process in adolescence not only involve physical changes but also require adjustments in terms of psychological and social. This study aims to examine the effect of ACT (Acceptance and Commitment Therapy) as a therapy for adolescents on mental and physical health problems including cognitive, emotional and behavioural aspects. The method used was Systematic Literature Review using 4 databases including Science Direct, PubMed, Springer Link, and Scopus, and critical appraisal was carried out and resulted in 7 literatures with the category of adolescents aged 10-21 years. The results show that based on the 7 literatures that have been reviewed, ACT is proven to be effective as a therapy for adolescents. Based on the diversity in the characteristics of adolescents studied, it shows that the application of ACT contributes positively to adolescents with ASD (autism spectrum disorder), SLD (specific learning disorder), obesity and mental health problems including psychological distress such as stress, anxiety, depression, self-defences mechanisms, flexibility in dealing with problems. Several factors that may be associated with the effectiveness of ACT therapy include the number of sessions, duration, media of presentation and self-assignment. Adolescents showed a positive effect on online and offline method at 4-8 sessions, duration of 30-90 minutes and delivery media involving pictorial media in ACT-online as well as flexibility in the time of therapy implementation.